Traveltime tomographic inversion with simultaneous static corrections - Well worth the effort - Tryggvason, A.; Schmelzbach, C.; Juhlin, Christopher (Society of Exploration Geophysics, 2009)
We have developed a first-arrival traveltime inversion scheme that jointly solves for seismic velocities and source and receiver static-time terms. The static-time terms are included to compensate for varying time delays introduced by the near-surface low-velocity layer that is too thin to be resolved by tomography. Results on a real data set consisting of picked first-arrival times from a seismic-reflection 2D/3D experiment in a crystalline environment show that the tomography static-time terms are very similar in values and distribution to refraction-static corrections computed using standard refraction-statics software. When applied to 3D seismic-reflection data, tomography static-time terms produce similar or more coherent seismic-reflection images compared to the images using corrections from standard refraction-static software. Furthermore, the method provides a much more detailed model of the near-surface bedrock velocity than standard software when the static-time terms are included in the inversion. Low-velocity zones in this model correlate with other geologic and geophysical data, suggesting that our method results in a reliable model. In addition to generally being required in seismic-reflection imaging, static corrections are also necessary in traveltime tomography to obtain high-fidelity velocity images of the subsurface. © 2009 Society of Exploration Geophysicists.